A Proposal for a New Universal Development Commitment. Issue 4 (26th July 2020) - Sumner, Andy; Gulrajani, Nilima; Wickstead, Myles; Glennie, Jonathan
Abstract: Most developed countries have accepted, in principle at least, the 50‐year‐old commitment of contributing 0.7 per cent of gross national income to supporting the development of developing countries. But what if all countries made a universal development commitment, meaning a scaled contribution? We propose a new universal and scaled financial commitment to development, informed by but not necessarily identical to official development assistance. This paper: (1) sets out how a new era is emerging of higher global ambitions – for example, to end poverty; (2) proposes a new way to raise and govern international public funds; and (3) discusses the possible size and use of contributions, and the evolution in global governance and democracy that a new deal would entail. We conclude with a set of questions that the proposal raises. Abstract : In the end, making progress on a universal development commitment of this kind, as with so much else, will depend on politics and what numbers and percentages prove acceptable to all parties involved.